Virtual and augmented reality in education, art, and museums - Guazzaroni, Giuliana, 1968-; Pillai, Anitha S., 1967- (IGI Global, 2020)
"This book explores the strategic role and use of virtual and augmented reality in shaping visitor experiences at art galleries and museums and their ability to enhance education"--
Digit(al)isation in Museums: Civitas Project: AR, VR, Multisensorial and Multiuser Experiences at the Urbino's Ducal Palace / Paolo Clini, Polytechnic University of Marche, Italy and 18 others -- Employing Real-Time Game Technology for Immersive Experience (VR and videogames) for all at MAIO Museum - Museum of WWII stolen artworks / Giuliana Geronimo, Streamcolors srl, Italy; Salvatore Giannella, Journalist, Italy -- Journeys into Poetry through 360° images and Virtual Reality / Licia Landi, UniVR, Italy.
Keywords: Virtual reality in education; Museums -- Educational aspects